Baseline Renal and Hepatic Function Predict Mortality in VA-ECMO - Delfiner, Matthew S.; Peters, Kyle; Toyoda, Yoshiya; Hamad, Eman (Journal of cardiac failure, 2019)
Venoarterial Extracorporeal Membrane Oxygenation (VA-ECMO) provides mechanical circulatory support for patients in cardiogenic shock, though risk stratification for potential ECMO patients is inconsistent. We seek to determine if baseline organ dysfunction and post-ECMO cannulation organ dysfunction predict mortality at 30 days of diagnosis of shock. Patients with renal and hepatic dysfunction at baseline have higher 30 day mortality than those with normal organ function. All VA-ECMO patients at a single urban quaternary care center from August 2016 to November 2018 were collected into a database. The electronic medical record was queried for demographic information and laboratory values concerning kidney and liver function. All variables were compared between patients who died while on ECMO and patients who survived to 30 days. Continuous variables were analyzed with t-test and categorical variables compared with chi-square analysis and risk ratios. There were 89 patients on VA-ECMO during the study period. Of these, 58 patients (65%) died while on ECMO and 31 survived (35%). There was no difference in age, sex, and race. The baseline mean creatinine (Cr) for patients who survived was 1.49 mg/dL compared to 2.38 mg/dL for those in the deceased group (p<0.001). There was no difference in the change in Cr after cannulation between the two groups. The mean baseline alanine aminotransferase (ALT) in the survived group was 188 U/L and was 357 U/L in the deceased group (p=0.089); the survived subjects had a mean baseline aspartate aminotransferase (AST) of 146 U/L while the deceased subjects was 424 U/L (p=0.011). While on ECMO, the ALT in the survived and deceased populations were 119 U/L and 545 U/L, respectively (p = 0.02). The AST trended similarly with a mean of 184 U/L for survived subjects and 1136 U/L for deceased subjects (p<0.001). The baseline total bilirubin (T.bili) for those who survived was 1.28 mg/dL and for deceased was 1.72 mg/dL (p=0.008). While on ECMO, the T.bili for the survived population was 2.05 mg/dL compared to 5.72 mg/dL for the deceased (p<0.001). The baseline mean lactate in the survival group was 7.8 mmol/L and 5.5 mmol/L in the deceased group (p=0.093); while cannulated the survived group had a mean lactate of 4.14 mmol/L compared to 9.98 mmol/L in the deceased group (p=0.003). See Figure 1 for mortality risks. Baseline renal and hepatic function predicts ECMO mortality, as does worsening hepatic function while cannulated. By using these trends to risk stratify patients, physicians can more appropriately decide who will most benefit from this procedure.